Endocrine mechanisms in the pathogenesis of primary varicosis - Busch, Ch.; Schnabl, S.; Strölin, A. (Phlebologie, 2013)
Introduction: Varicose veins affect up to 40 % of men and up to 51 % of women. The patho-physiology of primary varicosis (chronic venous insufficiency, CVI) is poorly understood. Here, the available data on possible endocrine mechanisms in healthy and varicose veins are reviewed.Methods: An extensive literature search was conducted in PubMed using the following key words: Chronic venous insufficiency, CVI, chronic venous disease, CVD, varicosis, saphenous vein, pathogenesis, hormone.Results: Several theories ranging from incompetence of the valves to functional, biological or morphologic changes in different layers of the vein wall have been proposed. However, an increasing body of evidence suggests that endocrine mechanisms might be involved in the pathogenesis of primary varicosis. In this respect a growing number of hormones (e.g. estrogen, progesterone, relaxin-2, and oxytocin) and their receptors have been linked to primary varicosis in experimental, pharmacological and histological studies.Conclusion: In summary, endocrine-based mechanisms seem to play a role in the pathogenesis of primary varicosis. This opens up the perspective for pharmacological treatments targeting the various described endocrine regulatory networks.
Keywords: Varicosis; CVI; saphenous vein; pathogenesis; hormone; receptor